Economic Model for Optimum Standardized Total Tract Digestible Phosphorus for Finishing Pigs - C. M. Vier; S. S. Dritz; M. D. Tokach; U. A. Orlando; W. Cast; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2019)
An adequate supply of dietary phosphorus (P) is important for pig growth performance and bone mineralization. However, P represents the third most expensive nutrient in swine diets after energy and protein and can greatly affect diet cost. Therefore, the objective of this project was to develop a tool to compare current dietary standardized total tract digestible (STTD) P concentrations to suggested values that yield maximum growth performance while accounting for different financial scenarios. The phosphorus economic tool is a Microsoft Excel-based model that evaluates the user’s current dietary STTD P concentrations for a specific production system and market conditions. The tool takes into consideration whether the system is marketing pigs on a fixed time or fixed weight basis. Moreover, the user has the option of an imperial or metric version, as well as the evaluation using two different energy systems: metabolizable energy and net energy. Data from Vier et al. have described the dose response curve to increasing STTD P for late nursery and finishing pigs under commercial conditions. Based on these data, regression equations were developed to predict the STTD P requirement, as a percentage of the diet, for maximum growth rate according to the energy content of the user’s diets. For model calculations, non-linear regression equations for average daily gain and feed efficiency are used. The tool calculates profitability indicators utilizing live or carcass weights. For profitability calculations on a carcass basis, a regression equation was developed to account for the effect of STTD P on carcass yield. This tool provides a means for the users to compare their current STTD P concentrations to levels required to achieve maximum growth performance, while considering the financial implications under dynamic productive and economic situations. The model can be accessed at www.ksuswine.org or at the open science framework data repository.